Mediating role of SEMS in the effect parenting styles and early childhood motor development and social skills - Sudirman Pabokori; Dwi Yuliani Adnan; Asriadi; Wa Ode Sitti Justin; Runita La Anihi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines the mediating role of Social Exchange of Motoric Support (SEMS) in the relationship between parenting styles and early childhood motor development and social skills. Using a quantitative explanatory design, data were collected from 70 children enrolled in Early Childhood Education (PAUD) institutions in Baubau City. Parenting styles were measured using the Parenting Style and Dimensions Questionnaire (PSDQ), social skills using the Social Skills Rating System (SSRS), and motor development using an assessment instrument from the Indonesian Ministry of Health. Structural Equation Modeling (SEM) with SmartPLS was employed for data analysis. The findings reveal that parenting styles significantly influence children’s motor development and social skills, while SEMS serves as a significant mediator that strengthens these relationships. The study highlights the importance of social interactions grounded in motoric support and underscores the critical role of parents and caregivers in fostering optimal motor and social development in early childhood.